TEACHING ENGLISH IN UZBEKISTAN'S SECONDARY SCHOOLS: A DECOLONIAL APPROACH - Ne’matov, Abdullajon (University Research Base, 2025)
This article explores decolonial approaches to English language teaching (ELT) in Uzbekistan’s secondary schools, balancing global language learning with cultural sovereignty in a post-Soviet context. It examines challenges and opportunities in creating culturally responsive English education that preserves indigenous values while preparing students for global engagement. The study highlights strategies such as integrating local literature, fostering critical media literacy, community-based learning, and digital cultural exchange. Case studies show that decolonial methods enhance both language skills and cultural identity. The article concludes with policy recommendations to support linguistic competence without cultural loss, positioning English education as a means of cultural affirmation.